HISAB AWAL WAKTU SALAT DALAM KITAB AL-KHULASAH FI AL-AQWAT AL-SYAR’IYYAH BI AL-LUGHARITMIYYAH KARYA MUHAMMAD KHUMAIDI JAZRY - Mubit, Rizal (IAIN Tulungagung, 2016)
Prayer is the pre-determined-timed obligatory worship. The juristsdecide the time of prayer based on the rotation of the earth or naturalphenomena. Such concept is still thought to be applicable until today.On the contrary, the astronomers decide the time of prayer basedon a more mathematical formula. Since the invention of arithmetic,prayer time decision formula and methods are always evolving untilnow. Good progress occurs in the formula as well as in the use oftools. There are several methods used by the experts to confirm it.One is the concept of the calculation using logarithm tables. Thebook that discusses the methods is the book Al-Khulasah fi al-Awqatal-Syar’iyyah bi al-Lugharitmiyyah by Muhammad Khumaidi Jazry.In this book, in addition to making the calculation formula, theauthor also specifies the use of a table of five decimal logarithms.The results compared with calculations using the ephemeris methoddo not produce a significant difference. The difference between everyprayer time is only in the range of two to four minutes.Kata kunci: Waktu Salat, Tabel Logaritma, Al-Khulasah fi Al-Awqatal-Syar’iyyah bi al-Lugharitmiyyah